Sex differences in workload-indexed blood pressure response and vascular function among professional athletes and their utility for clinical exercise testing - Bauer, P.; Kraushaar, L.; Dörr, O.; Nef, H.; Hamm, C. W.; Most, A. (European Journal of Applied Physiology, 2022)
Purpose: Sex differences in blood pressure (BP) regulation at rest have been attributed to differences in vascular function. Further, arterial stiffness predicts an exaggerated blood pressure response to exercise (BPR) in healthy young adults. However, the relationship of vascular function to the workload-indexed BPR and potential sex differences in athletes are unknown. Methods: We examined 47 male (21.6 ± 1.7 years) and 25 female (21.1 ± 2 years) athletes in this single-center pilot study. We assessed vascular function at rest, including systolic blood pressure (SBP). Further, we determined the SBP/W slope, the SBP/MET slope, and the SBP/W ratio at peak exercise during cycling ergometry. Results: Male athletes had a lower central diastolic blood pressure (57 ± 9.5 vs. 67 ± 9.5 mmHg, p < 0.001) but a higher central pulse pressure (37 ± 6.5 vs. 29 ± 4.7 mmHg, p < 0.001), maximum SBP (202 ± 20 vs. 177 ± 15 mmHg, p < 0.001), and ?SBP (78 ± 19 vs. 58 ± 14 mmHg, p < 0.001) than females. Total vascular resistance (1293 ± 318 vs. 1218 ± 341 dyn*s/cm5, p = 0.369), pulse wave velocity (6.2 ± 0.85 vs. 5.9 ± 0.58 m/s, p = 0.079), BP at rest (125 ± 10/76 ± 7 vs. 120 ± 11/73.5 ± 8 mmHg, p > 0.05), and the SBP/MET slope (5.7 ± 1.8 vs. 5.1 ± 1.6 mmHg/MET, p = 0.158) were not different. The SBP/W slope (0.34 ± 0.12 vs. 0.53 ± 0.19 mmHg/W) and the peak SBP/W ratio (0.61 ± 0.12 vs. 0.95 ± 0.17 mmHg/W) were markedly lower in males than in females (p < 0.001). Conclusion: Male athletes displayed a lower SBP/W slope and peak SBP/W ratio than females, whereas the SBP/MET slope was not different between the sexes. Vascular functional parameters were not able to predict the workload-indexed BPR in males and females.